Natriuretic peptide receptor 3 genotype modulates the relationship between B-type natriuretic peptide and left ventricular end-diastolic pressure. Issue 6 (November 2006) - Lanfear, David E; Stolker, Joshua M; Marsh, Sharon; Rich, Michael W; McLeod, Howard L
Background: B-type natriuretic peptide levels are associated with left ventricular end-diastolic pressure (LVEDP) and patient outcomes. There is documented variation in the genetic sequence of natriuretic peptide receptor (NPR)3, which is a primary clearance mechanism for B-type natriuretic peptide (BNP).Methods: DNA was extracted from 147 patients, aged 60 years or over undergoing elective left-heart catheterization for any indication, excluding acute myocardial infarction or severe valvular disease. Genotype was determined at four loci in the NPR3 gene. The logBNP:LVEDP ratio was compared between genotype groups. Linear and logistic regression models of LVEDP were generated.Results: The LogBNP:LVEDP ratio was significantly different among NPR3 IVS2––84 A allele carriers compared with G allele homozygotes (p = 0.008), with the A allele carriers showing a higher BNP level for a given level of LVEDP. The other variants did not alter this relationship (all p > 0.4). When added to the optimal linear regression model for LVEDP, NPR3 IVS2––84 genotype incrementally added to the model (p = 0.024, model r = 0.54). This was also true of the optimal logistic regression model of LVEDP ≥≥ 20 mmHg (p = 0.026).Conclusions: NPR3 IVS2––84 G>A genotype is associated with altered logBNP:LVEDP ratio and provides incremental value to predictive models of LVEDP. Further studies should address whether this or other variants in the BNP pathway modify the clinical importance of endogenous or exogenous BNP.